Disharmony of Domestic Refining Provisons for Mineral and Coal in Indonesian Laws and Regulations - Ira Fadilla Rohmadanti; Febriansyah Ramadhan; Ilham Dwi Rafiqi (Pandecta Research Law Journal, 2022)
Domestic refining practices of minerals and coal in Indonesia have not run efficiently and provided provisions for the country. The challenge of realizing the purification policy comes in turn, one of which is the problem of regulation. Hence, this study aims to examine and analyze mineral and coal (referred to as minerba) refining policy in the country in the laws and regulations, ranging from the level of legislation to implementing regulations. The research method used is normative legal research using a statutory and conceptual approach. The results showed that domestic minerba refining policies stated in many rules tends to be not one-way and is flexible, indicated by frequent changes in domestic refining policy. As a result, it causes disharmony between the Minerba Bill and the implementing regulations. Some implementing regulations, particularly Ministerial Regulations, are not in accordance with the principle of the obligation to increase the value-add by carrying out processing and refining domestically. Moreover, the regulation is considered contradictory due to providing opportunities for exporting minerals that have not been processed and refined, leading to reduced state revenues and impact on state losses.